CRITERIA AND RULES OF INTERPRETING CONTRACTS IN EU CONTRACT LAW - Ustymenko, Olena (The Journal of V. N. Karazin Kharkiv National University. Series Law, 2025)
Introduction. The sources of EU contract law contain criteria and rules for interpreting the content of contracts. Uniform approaches to interpreting the content of concluded contracts are designed to provide the parties with a certain toolkit that helps to reach a common understanding of the content of the contract for the purpose of its proper execution or resolution of a contractual dispute. The criteria and rules for interpreting contracts provided for in EU contract law are also applied when resolving contractual disputes in national law, which indicates the importance of their study in doctrine and practice. Summary of the main results of the study. The main criterion used when interpreting contracts in EU contract law is the intention of the parties. This criterion is applied if it is possible to establish this intention of the parties, that is, if there is no doubt about the intention of the parties, then contradictions in interpretation are eliminated. The intention of the parties during interpretation prevails over the literal content of the text of the contract. If the intention of the parties cannot be established, the provisions of the contract must be interpreted in accordance with how reasonable persons similar to the parties would have understood them in similar circumstances. The criterion of a «reasonable person» in commercial contracts must be understood as an entrepreneur who has certain knowledge and experience in the relevant field. By similar circumstances in which a reasonable person acts, in the context of interpreting a contract, one must understand the nature and purpose of the contract, the previous conduct of the parties, pre-contractual relations, the meaning given to terms and conditions in the relevant field, customs, good faith, etc. Conclusion. EU contract law acts also offer certain rules that must be applied during interpretation in the event of ambiguity in the text of the contract. These include «favor negotii» (in favor of the validity of the transaction), the rule of preference of the first version of the text of the contract, the rule of systematic interpretation, «contra proferentem» (against the one who proposed), the rule of preference of terms that were agreed individually. The above rules can be applied and enforced in national law, where the experience of EU contract law can be useful.